Interactive PowerPoint Based on Game-Based Learning on Environmental Pollution for Junior High School Students - Suhartatik Suhartatik; Shinta Permata Sari; Maysara Maysara; Eka Nurul Qomaliyah (PT Ahan Group Publisher, 2026)
This research aims to develop an interactive PowerPoint-based learning media using Game-Based Learning (GBL) for junior high school students on environmental pollution. The method used is Research and Development (R&D) with a 4-D development model, which includes the stages of Define, Design, Develop, and Disseminate. However, the Disseminate stage was not implemented due to time constraints in the research. The media validation was conducted by three experts, comprising two science education professors and one junior high school science teacher, while the readability test was conducted with 18 seventh-grade students. The validation results showed the media's qualification level at 93%, placing it in the “almost perfect” category. Meanwhile, the readability test results averaged 94%, placing it in the “very good” category. The developed media are equipped with interactive features, including visual materials, animated videos, educational games, question-and-answer exercises, and GBL-based evaluation quizzes. Based on the validation results and readability tests, this media is deemed suitable for use in science instruction at the junior high school level.